Lung Adenocarcinoma Metastases to Mediastinal with Malignant Pericardial Effusion - Andri, Andri; Parsama Putra, Ngakan Putu; Sargowo, Djanggan; Erawati, Dini Rachma; Retnani, Diah Prabawati (Universitaas Brawijaya, 2021)
Lung adenocarcinoma with malignant pericardial effusion and also metastases to mediastinum has great impact on morbidity and mortality of patient and it is rare case. Most adenocarcinoma in the mediastinum are metastases from the lung, gastrointestinal tract, pancreas, kidney or even the pituitary gland. Cardiac metastases in lung cancer may occur due to retrograde lymphatic spread or by hematogenous dissemination of tumour cells. Pericardium is frequently involved in direct cardiac invasion by adjacent lung cancer. Pericardial effusion, pericarditis, and tamponade are common and life threatening presentation in such cases. A 42-years-old male with superior mediastinal mass has malignant pericardial effusion, cytology shows adenocarcinoma. The patient undergo transthoracic fine needle aspiration biopsy. The result from biopsy is adenocarcinoma. This is a rare case, patient with primary lung adenocarcinoma and malignant pericardial effusion also metastases to mediastinum. To determine the diagnosis requires a comprehensive clinical evaluation and multidisciplinary approach.